2016
DOI: 10.1007/s00059-016-4424-6
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase 1 induction protects myocardiac cells against hypoxia/reoxygenation-induced apoptosis

Abstract: In summary, our results suggest that HO-1 can decrease H/R-induced myocardiac cell apoptosis; the mechanism may be related to the activation of the Akt signaling pathway and, furthermore, to the inhibition of the JNK/c-Jun/caspase-3 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…JNK is a member of the MAPK family, which modulates various cellular functions, including proliferation, differentiation, and cell apoptosis [30]. Research on H/R or I/R models in the myocardium [31], renal cells [32], and the brain [33] showed that activated JNK mediates injury and that inhibition of p-JNK expression can reduce H/R- or I/R-induced apoptosis, death, or necrosis. Previous studies in our laboratory also indicated that the inhibition of JNK activation can improve the survival of cardiac microvascular endothelial cells [5], which were supported by the results of Li et al [31] and Sun et al [34].…”
Section: Discussionmentioning
confidence: 99%
“…JNK is a member of the MAPK family, which modulates various cellular functions, including proliferation, differentiation, and cell apoptosis [30]. Research on H/R or I/R models in the myocardium [31], renal cells [32], and the brain [33] showed that activated JNK mediates injury and that inhibition of p-JNK expression can reduce H/R- or I/R-induced apoptosis, death, or necrosis. Previous studies in our laboratory also indicated that the inhibition of JNK activation can improve the survival of cardiac microvascular endothelial cells [5], which were supported by the results of Li et al [31] and Sun et al [34].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic cells were measured by Hoechst 33342 staining under a fluorescence microscope. Briefly, the cells were seeded in 6-well plates, stained with Hoechst 33342 for 5 min in the dark, and washed with PBS three times [ 34 ]. Then, the cells were observed using a fluorescence microscopy (IX73, Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Pro-BDNF shows high-affinity binding to sortilin and performs its biological functions by acting on its receptors: p75 NTR and sortilin [ 45 ]. Some studies have indicated that the JNK pathway contributes to the growth-inhibitory effect and apoptosis of ECs and that inhibition of JNK activation protects cardiomyocytes from I/R injury [ 46 49 ]. Pro-NGF/p75NTR/sortilin signaling increases JNK signaling [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy is a serious microvascular complication of DM; H/R promoted oxidative stress in NRK-52E cells exposed to HG accompanied by increased levels of Nrf2 and HO-1 protein expression [ 32 , 46 ]. High glucose has also been proved to increase the permeability of cardiac microvascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%